The role of innovation systems in rural economic development: a case study of the Exploits Valley Region, Newfoundland and Labrador - Aradottir, Elin (University of Guelph, 2003)
This Thesis argues that innovation is important in the context of the economic development of rural regions. It accordingly introduces a study of the Exploits Valley Region, Newfoundland and Labrador. The foundation of the study is the Innovation System Approach that builds on the assumption that innovation performance is influenced by interactions of agents and that economic activities, including innovation processes, are shaped by various institutions. The physical structure of the Exploits Valley Region provides opportunities for agglomeration effects and allows for development of innovation-related services. The economic development environment builds on an active, collaborative, development process. The regional innovation system is based on a pool of social capital and on certain institutional features that facilitate innovation. It is, however, dependent on overarching frameworks. There is a need to raise the entrepreneurial spirit, improve the availability of University-programs, increase the visibility of R&D, reduce red tape, and ensure equal prosperity throughout the region.